2022
DOI: 10.1021/acs.orglett.1c04074
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Synthesis of Thiocarboxylic Acid Derivatives

Abstract: A Ni-catalyzed cross-coupling of readily accessible O-alkyl xanthate esters or thiocarbonyl imidazolides and organozinc reagents for the synthesis of thiocarboxylic acid derivatives has been developed. This method benefits from a fast reaction time, mild reaction conditions, and ease of starting material synthesis. The use of transition-metal catalysis to access a diverse range of thiocarbonyl-containing compounds provides a useful complementary approach when compared with previously established methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Notably, our investigation revealed that this reaction tolerated low nickel and ligand loadings (as low as 1% Ni and 2% ligand), reached completion in less than 5 minutes at room temperature, and was readily performed on larger scales (e.g., reactions on a 10 mmol scale have since been performed with similar efficiency). Notably, the identities of the Ni-precatalyst, bipyridine ligand, and solvent system were found to have a smaller impact on the desired product yield in comparison to our previously developed deoxygenative arylation protocols. …”
Section: Section 2: Ni-catalyzed Cross-couplings Of Thiocarbonyl-acti...mentioning
confidence: 88%
See 3 more Smart Citations
“…Notably, our investigation revealed that this reaction tolerated low nickel and ligand loadings (as low as 1% Ni and 2% ligand), reached completion in less than 5 minutes at room temperature, and was readily performed on larger scales (e.g., reactions on a 10 mmol scale have since been performed with similar efficiency). Notably, the identities of the Ni-precatalyst, bipyridine ligand, and solvent system were found to have a smaller impact on the desired product yield in comparison to our previously developed deoxygenative arylation protocols. …”
Section: Section 2: Ni-catalyzed Cross-couplings Of Thiocarbonyl-acti...mentioning
confidence: 88%
“…A. L. Monteith, J. J. Scotchburn, K. Mills, L. R. Rousseaux, S. A. L. 10.1021/acs.orglett.1c04074Org. Lett.202224619624 …”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…1C, path a). 16 c – f Despite the high accessibility of AXEs and the well-established delivery of alkyl radicals as key intermediates in the reactions, noteworthily, utilizing them as cross-coupling handles in transition metal catalysis has been largely excluded from past work, 17 primarily due to the scarcity of suitable activation modes for the xanthate functionality. Although alkyl xanthate esters have been used in C–S bond formation via sequential alcoholysis-substitution, 18 to our knowledge, the employment of AXEs serving as alternative sulfenylating reagents for metal-catalyzed chemo- and regioselective cleavage of the C–S bond followed by cross-coupling with a carbon counterpart to deliver a new C–S bond remains an uncharted exercise (Fig.…”
Section: Introductionmentioning
confidence: 99%